Zhodnocení finanční situace podniku a návrh na financování reklamních aktivit - Baranyiová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Tato diplomová práce s názvem „Zhodnocení finanční situace podniku a návrh na financování reklamních aktivit“ se zabývá zpracováním zhodnocení současné finanční situace podniku prostřednictvím nástrojů finanční analýzy. Pomocí tohoto zhodnocení jsou následně zpracovány kroky pro realizaci a financování reklamních kroků.

This diploma thesis entitled "Evaluation of the financial situation of the company and a proposal for financing advertising activities" deals with the processing of the evaluation of the current financial situation of the company using financial analysis tools. With the help of this evaluation, the steps for the implementation and financing of advertising steps are subsequently processed.
Evaluation of the Financial Situation of the Company and Suggestions for Financing of Advertising Activities
Keywords: Finanční analýza; SWOT analýza; metoda SMART; Balanced Scorecard; reklama; rodinné podnikání; preference zákazníků; Financial analysis; SWOT analysis; SMART method; Balanced Scorecard; advertisement; family business; customer preferences